Effect of the farming intensification on health-promoting compounds in the meat of the Mediterranean mussel Mytilus galloprovincialis - Antonella della Malva; Antonella Santillo; Mariangela Caroprese; Marzia Albenzio (Aquaculture Reports)
This study investigated the effect of increasing levels of farming intensification on some health-promoting compounds present in the meat of the Mediterranean mussel Mytilus galloprovincialis in the Northern Coastal Area of Gargano, Italy, during the spring season. The studied farming systems were: extensive dropper ropes farming (EDR: 70 m distance between backbones, 90 cm distance between dropper ropes); semi-intensive dropper ropes farming (SIDR: 70 m distance between backbones, 50/60 cm distance between dropper ropes) and intensive dropper ropes farming (IDR: 30 m distance between backbones, 60/70 cm distance between dropper ropes). Mussels’ vitamins content (B1, B2, B3, B6 and C), fatty acids fractions, and angiotensin I converting enzyme (ACE) and 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) scavenging activities were investigated to assess the nutritional profile of mussels meat. The farming system affected the vitamin B2 content, with the EDR and IDR farming sites showing greater content than SIDR. Mussels from EDR site showed a percentage of n3 fatty acids always higher than 50 % across the sampling months. However, the average n3 value in mussels from EDR and SIDR was higher compared to IDR farming site. Mussels from EDR and SIDR evidenced lower values of Atherogenic and Thrombogenic indexes compared to mussels reared under intensive conditions. Mussels collected from the SIDR farming site exhibited higher antioxidant and ACE-inhibitory activities than those collected from IDR farming site. This study suggests that lower stocking density offers better farming conditions able to modulate the nutritional composition and health benefits of mussels reared in the Northern Coastal Area of Gargano.